2001
DOI: 10.1029/2000ja000461
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of geocoronal and heliospheric X‐ray emission associated with the solar wind interaction with neutrals

Abstract: Abstract. X-ray emission due to charge transfer collisions between heavy solar wind ions and neutrals has been predicted to exist both in the heliosphere and in the geocorona. The heliospheric X-ray emission can account for roughly half of the observed soft X-ray background intensity. It was also suggested that temporal variations in the heliospheric and geocoronal soft X-ray intensities will result from solar wind variations. In this paper, a simple model of the charge exchange X-ray emission mechanism is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
244
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(252 citation statements)
references
References 37 publications
8
244
0
Order By: Relevance
“…The last comparison was a simple r −3 model with a 25 cm −3 number density at a distance of 10 R E [Cravens et al, 2001]. The results of each comparison show very minor differences in shape and magnitude, certainly not enough for the Hodges model to be the cause of the variations between the modeled and observed light curves.…”
Section: 1002/2015ja022292mentioning
confidence: 99%
See 2 more Smart Citations
“…The last comparison was a simple r −3 model with a 25 cm −3 number density at a distance of 10 R E [Cravens et al, 2001]. The results of each comparison show very minor differences in shape and magnitude, certainly not enough for the Hodges model to be the cause of the variations between the modeled and observed light curves.…”
Section: 1002/2015ja022292mentioning
confidence: 99%
“…We use 2 h time resolution, O/H ratio, and oxygen charge state abundance data from the ACE spacecraft, timeshifted to the bow shock in the same way as the OMNI data. [Cravens et al, 2001;Robertson and Cravens, 2003].…”
Section: Calculatingmentioning
confidence: 99%
See 1 more Smart Citation
“…This signal level has generally been attributed to emission associated with the Local Hot Bubble. , Cravens et al (2001) and Robertson and Cravens (2003) have assessed the potential level of contamination to the ROSAT All Sky Survey by solar wind charge exchange in the slow and fast winds. Robertson and Cravens (2003) found that 0.1 to 1.0 keV X-rays produced in the heliosphere by the steady slow and fast winds could account for ∼ 1/2 of the soft X-rays in the Galactic plane and a smaller fraction of the high latitude locallymade soft X-rays.…”
Section: Solar Wind Charge Exchange (Swcx)mentioning
confidence: 99%
“…The terrestrial exospheric hydrogen density, which exceeds the average density of the solar wind at the magnetopause, drops off rapidly and continuously with distance from Earth. Figure 1 shows the correlation between the solar wind flux observed by NASA's Interplanetary Monitoring Platform 8 (IMP 8) spacecraft and the ROSAT soft X-ray flux, illustrating not only the presence of this signal but also its exceptional correlation with local solar wind conditions, its high count rate even when observing perpendicular to the most intense emission at the nose of the magnetopause (because of ROSAT's operational constraints), and its almost immediate response to rapid variations in the solar wind [Cravens et al, 2001] …”
Section: Detecting Soft X-raysmentioning
confidence: 99%